Penerapan Model Pembelajaran Mind Mapping dengan Media Kartu untuk Meningkatkan Hasil Belajar Siswa - Ana Arifah Zuhdiana; Lilik Mawartningsih (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
Based on observation result in MTs. Tarbiyatul Banin Banat Village Jetak District Montong Tuban on teaching and learning process, especially on grade VII students A science subjects are still conventional lectures that cause the lack of activeness of students in teaching and learning activities so that student learning outcomes are less than optimal. It is feared that student learning outcomes from year to year will decline. The purpose of this study is to find out the improvement of student learning outcomes with the application of Mind Mapping learning model with card media. This study is a Classroom Action Research (CAR) where the parameters measured are the results of student learning, teacher activity, student activity and student responses to the application of learning model Mind Mapping with card media on ecosystem material. Data collection techniques used in the form of observation methods, tests, and questionnaires. Based on the results of research obtained data on the percentage completeness of student learning outcomes classically in the cycle I 58.82%, cycle II 67.65%, and cycle III 88.24%. Percentage of observation of teacher activity cycle I 21%, cycle II 26%, and cycle III 29%. Percentage of observations of student activity cycle I 20%, cycle II 23%, and cycle III 30%. Results of student response data obtained data that 97.06% expressed as a positive response given by students. From the research result, it can be concluded that learning by applying Mind Mapping learning model with card media can improve student learning result, teacher activity, student activity and student response, and can be used as a reference in improving students quality in learning process through Mind Mapping learning model with media card.